The Rise of Concussions in the Adolescent Population. Issue 7 (18th July 2016) - Zhang, Alan L.; Sing, David C.; Rugg, Caitlin Marie; Feeley, Brian T.; Senter, Carlin
Objectives: Concussion injuries have been correlated with significant long-term deleterious effects on patients. While recent studies have shown increased traumatic brain injuries (TBI) diagnosed in U.S. emergency departments, no studies have evaluated trends in concussion diagnoses across the general U.S. population in various age groups. The objective of this study is to evaluate the current incidence and trends in concussions diagnosed across varying age groups and healthcare settings in a large cross-sectional population. Methods: Administrative health records of 8, 828, 248 members of a large private payer insurance group in the United States were queried. Patients diagnosed with concussion from years 2007 through 2014 were stratified by year of diagnosis, age group, gender, classification of concussion, and healthcare setting of diagnosis (e.g. ED vs. physician's office). Chi-square testing was used to for statistical analysis. Results: From a cohort of 8, 828, 248 patients, 43, 884 patients were diagnosed with a concussion. Fifty-five percent of concussion patients were male and over 32% were in the adolescent age group (10-19 years old). The highest incidence of concussion was seen in the 15-19 age group (16.5 cases per 1000 patients) followed by the 10-14 (10.5 per 1000), 20-24 (5.2 per 1000) and 5-9 (3.5 per 1000) age groups. Overall there was a 160% increase in concussion incidence from 2007 to 2014. The largest increases were in the 10-14 (243%) and 15-19 (187%) age groups. Based on ICD-9 classification, 29% of concussions were associated with some form of loss of consciousness. Finally, 56% of concussions were diagnosed in the ED and 29% in a physician's office, with the remainder in urgent cares or inpatient settings. Conclusion: The incidence of concussion diagnosed in the general population in the United States is increasing, driven largely by a substantial rise in the adolescent age group. The youth population should be prioritized for ongoing work in concussion education, diagnosis, treatment and prevention.